The Association between High Body Mass Index and Mortality Risk in Hospitalized Patients Diagnosed with COVID-19: A Meta-Analysis - Yuzana Maung; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2021)
Background: COVID-19, caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), emerged as a global pandemic with confirmed death cases of more than 1.27 million worldwide. Since the past pandemic, several studies discovered the adverse effects of excess fat accumulation on the severity of viral infections. This study aimed to investigate the association between high body mass index (BMI) and mortality risk in hospitalized COVID-19 patients based on four categories of high BMI ranges. Subjects and Method: A systematic review and Meta-Analysis was conducted using search articles from electronic databases including PubMed, Google Scholar, and Scopus, published from 2019 to 2021. The keywords used to retrieve articles were "Body Mass Index" OR BMI OR Obesity OR Overweight) AND (Mortality OR Death) AND COVID-19 OR SARS-CoV-2. The included studies were full-text articles published in the English language, reporting adjusted odds ratios from multivariate analysis. The eligibility criteria were defined using PICO model. The article selection was conducted using PRISMA flow chart. The included studies were analyzed by the Review Manager 5.3 application. Results: A total of nine cohort studies involving 12,907 COVID-19 patients with high BMI conducted from America, Europe, and Georgia regions was included in qualitative synthesis and Meta-Analysis. The pooled estimate showed hospitalized COVID-19 patients with morbid/ class III obesity had a higher risk of mortality (aOR= 1.77; 95% CI= 1.27 to 2.47; p= 0.001) than overweight (aOR= 1.10; 95% CI= 1.00 to 1.21; p= 0.060), class I (aOR= 1.16; 95% CI= 0.87 to 1.55; p= 0.300), and class II obesity (aOR= 1.54; 95% CI= 1.11 to 2.13; p= 0.009). Conclusion: High BMI increases the risk of mortality in hospitalized COVID-19 patients. A potential dose-response relationship may exist between different categories of high BMI range and mortality risk in COVID-19 patients.